Formula optimization of herbal drink based on coconut sugar and ginger using the Taguchi method [Optimasi formula minuman herbal berbasis gula merah dan jahe menggunakan metode Taguchi] - Niha, Aevita Ainun; Khuriyati, Nafis; Guritno, Adi Djoko (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Increasingly positive public consumption trends have increased demand for functional products such as ginger sugar herbal drinks. However, Micro, Small, and Medium Enterprises (MSMEs) producing ginger sugar herbal drinks still face production challenges, such as relying on traditional recipes passed down through generations with inconsistent processes, which affect quality uniformity. This study aimed to redesign the optimal formulation of ginger sugar herbal drinks based on parameters that affect the process. The method used is the Taguchi method with 4 (four) factors and 3 (three) levels with an L9 (34) orthogonal array matrix. Then, quality parameters were tested to determine the best ginger sugar herbal drink product. The combination of level factors in the optimal formula of ginger sugar herbal drink is the composition of ginger juice 300 mL, brown sugar 700 grams, granulated sugar 500 grams, and cooking time 45 minutes. The results of testing the quality characteristics of the confirmation experiment were following SNI requirements, namely water-insoluble part content 0.84%; water content 4.99%; ash content 1.65%; reducing sugar content 2.48%; sucrose sugar content 81.15%; dissolving time 29.93 seconds; antioxidant activity 67.13 ppm; color sensory properties 5.43; aroma sensory properties 5.32; taste sensory properties 5.16; aftertaste sensory properties 5.53; and overall sensory properties 5.21.Keywords: coconut sugar, ginger, herbal drink, quality, Taguchi method